Evidence for metabolic diversity in Meso-Neoproterozoic stromatolites (Vazante Group, Brazil) - Callefo, Flavia; Ricardi-Branco, Fresia; Alves Forancelli Pacheco, Mírian Liza; Cardoso, Alexandre Ribeiro; Noffke, Nora; de Carvalho Teixeira, Verônica; Neckel, Itamar Tomio; Maldanis, Lara; Bullock, Emma; Bower, Dina; Moreira Silva, Adalene; Ferreira Sanchez, Dario; et al. (Frontiers in Earth Science, 2022)
Deciphering the evolution of ecological interactions among the metabolic types during the early diversification of life on Earth is crucial for our understanding of the ancient biosphere. The stromatolites from the genus Conophyton cylindricus represent a datum for the Proterozoic (Meso to Neoproterozoic) on Earth. Their typical conical shape has been considered a result of a competition between microorganisms for space, light and nutrients. Well-preserved records of this genus from the “Paleontological Site of Cabeludo”, Vazante Group, São Francisco Craton (Southern Brazil) present in situ fossilized biofilms, containing preserved carbonaceous matter. Petrographic and geochemical analyses revealed an alternation between mineral laminae (light grey laminae) and fossilized biofilms (dark grey laminae). The dark grey laminae comprise three different biofilms recording a stratified microstructure of microbial communities. These three biofilms composing the dark grey laminae tend to be organized in a specific pattern that repeats through the stromatolite vertical section. Iron and manganese are distributed differently along the dark and light grey laminae; X-ray absorption and luminescence data showed possible different areas with authigenic iron and iron provided from diagenetic infiltration. Cryptocrystalline apatite in the lowermost biofilms in each dark grey laminae may suggest past metabolic activity of sulfide-oxidizing bacteria. These findings suggest that the microorganisms reached a complex metabolic diversification in order to maintain an equilibrium situation between the three different biofilms along the vertical section of the structures, thus benefiting the whole microbial community. This means that the stromatolites from the Conophyton genus may have formed as a result of a greater complexity of interactions between microorganisms, and not only from competition between photosynthesizers.